2021
DOI: 10.3390/metabo11040248
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Reproducibility of Urinary Metabolomic Biomarkers of Habitual Food Intake in a Cross-Sectional Analysis of the Cancer Prevention Study-3 Diet Assessment Sub-Study

Abstract: Previous cross-sectional metabolomics studies have identified many potential dietary biomarkers, mostly in blood. Few studies examined urine samples although urine is preferred for dietary biomarker discovery. Furthermore, little is known regarding the reproducibility of urinary metabolomic biomarkers over time. We aimed to identify urinary metabolomic biomarkers of diet and assess their reproducibility over time. We conducted a metabolomics analysis among 648 racially/ethnically diverse men and women in the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
(52 reference statements)
3
13
1
Order By: Relevance
“…15 This unnamed compound was also present in GI diets but to a lesser degree. A study 18,19 in people identified X-25419 in blood and urine to be associated with fish and olive oil ingestion, and a study 20 of dogs with mitral valve disease found that X-25419 was significantly different between healthy dogs predisposed to heart disease and dogs with mild heart disease. Fish is a common protein source for many types of dog diets, but diet was not reported in the dog study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 This unnamed compound was also present in GI diets but to a lesser degree. A study 18,19 in people identified X-25419 in blood and urine to be associated with fish and olive oil ingestion, and a study 20 of dogs with mitral valve disease found that X-25419 was significantly different between healthy dogs predisposed to heart disease and dogs with mild heart disease. Fish is a common protein source for many types of dog diets, but diet was not reported in the dog study.…”
Section: Discussionmentioning
confidence: 99%
“…Fish is a common protein source for many types of dog diets, but diet was not reported in the dog study. 18 Until structural elucidation is performed, speculation about the clinical importance of X-25419 is not possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2-methoxyresorcinol is a polyphenol that derives from the consumption of green and black tea [ 33 , 135 ]. Urinary 2-methoxyresorcinol was identified as a biomarker of tea consumption [ 33 ].…”
Section: Proteinsmentioning
confidence: 99%
“…2-methoxyresorcinol is a polyphenol that derives from the consumption of green and black tea [ 33 , 135 ]. Urinary 2-methoxyresorcinol was identified as a biomarker of tea consumption [ 33 ]. However, no studies have been carried out to elucidate its bioavailability and contribution to plasma retention in humans.…”
Section: Proteinsmentioning
confidence: 99%